2016
DOI: 10.1186/s41256-016-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Community-based management versus traditional hospitalization in treatment of drug-resistant tuberculosis: a systematic review and meta-analysis

Abstract: BackgroundMultidrug drug resistant Tuberculosis (MDR-TB) and extensively drug resistant Tuberculosis (XDR-TB) have emerged as significant public health threats worldwide. This systematic review and meta-analysis aimed to investigate the effects of community-based treatment to traditional hospitalization in improving treatment success rates among MDR-TB and XDR-TB patients in the 27 MDR-TB High burden countries (HBC).MethodsWe searched PubMed, Cochrane, Lancet, Web of Science, International Journal of Tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
3
14
0
1
Order By: Relevance
“…Bulgaria is considering a transition from hospital-based TB management to a comprehensive ambulatory TB care program. Previous studies have consistently shown that there is no significant difference in treatment outcomes between the two models of care [22, 25]. Consistent with this, in our model we simulate no parameter changes as a consequence of changing to this approach.…”
Section: Discussionsupporting
confidence: 81%
“…Bulgaria is considering a transition from hospital-based TB management to a comprehensive ambulatory TB care program. Previous studies have consistently shown that there is no significant difference in treatment outcomes between the two models of care [22, 25]. Consistent with this, in our model we simulate no parameter changes as a consequence of changing to this approach.…”
Section: Discussionsupporting
confidence: 81%
“…Community-based treatment models allow a patient to complete treatment in their own homes, under the supervision of a close contact. This incurs fewer transportation costs to the patients, and in some cases provides better home care and improved social wellbeing as well as an improved ability to continue with daily activities [45][46][47][48]. Speci cally, rural community-based models have been shown to be more effective than urban community-based models, in part due to the organized referral system in rural settings and perhaps due to the increased advantages of not traveling to a distant clinic for care [29].…”
Section: Discussionmentioning
confidence: 99%
“…Community-based DOT (CB-DOT), designed to relieve the pressure of patient care on overstretched health facilities in countries with a high TB burden [24], is a cost-effective approach associated with better compliance to treatment and better patient satisfaction compared to hospital-based DOT (HB-DOT) [25]. Systematic review [2628] also showed that CB-DOT did improve TB treatment outcomes. In China, TPM by LHWs in the integrated TB control model [6] is one type of CB-DOT.…”
Section: Discussionmentioning
confidence: 99%